Localized law : the Babatha and Salome Komaise archives - Czajkowski, Kimberley (Oxford studies in Roman society and law, 2017)
'Localized Law' examines the legal archives of Babatha and Salome Komaise, which offer a window onto the practice of law in Maoza as it came under the control of the Roman Empire. A series of case studies of the various agents involved in the legal transactions illuminates the legal culture of this community and its practice of law and justice